Perfil clínico e epidemiológico dos casos notificados de meningite na região metropolitana de Belém no período de 2012 a 2022 - OLIVEIRA, Dhefferson Luanderson Teixeira de (2024)
Introduction: Meningitis is a disease characterized by inflammation of the leptomeninges, this process having an infectious origin, with viral and bacterial etiologies being the most relevant in terms of public health, and non-infectious inflammations such as those caused by trauma, tumors, and chemicals. Objectives: To describe the clinical and epidemiological profile of meningitis cases reported by the Information System for Notifiable Diseases in the municipalities of the metropolitan region of Belém (Belém, Ananindeua, Benevides, Castanhal, Marituba, Santa Bárbara do Pará, and Santa Izabel do Pará) between the years 2012 and 2022. Methodology: This is a retrospective, cross sectional, quantitative, and descriptive study based on the collection of secondary data obtained from the Information System for Notifiable Diseases. Data will be collected between August 2022 and June 2023. Results: During the period from 2012 to 2022, 3469 cases of meningitis were reported and confirmed in the metropolitan region of Belém, with an average of 315 cases per year, with a slight variation in the annual average during the studied period. The city of Belém recorded the highest number of cases, accounting for 3,434 (98.99%) of the cases, followed by Ananindeua with 15 cases (0.43%). Regarding sociodemographic data, males accounted for 2001 cases and females accounted for 1468 (42.32%) confirmed cases. The racial/ethnic group with the highest number of cases was parda (mixed race), with 81.55%, followed by white with 7.78%, and black with 1.35%. The most frequent age group during the analyzed period was 20 to 39 years, with 34.74%, and the most expressive level of education was incomplete middle school (5th to 8th grade), representing 11.42% of the total. Concerning the confirmation criteria employed to diagnose meningitis in the metropolitan region of Belém, the prevalence of the chemocytological method is noteworthy, reaching a significant rate of 67.17%, and regarding the most prevalent etiology, viral is followed by bacterial. There were 397 deaths caused by meningitis registered, with bacterial etiology responsible for a large portion of these deaths. Conclusion: Meningitis still constitutes a public health problem in the metropolitan region of Belém, mainly in the city of Belém, which concentrates the highest number of cases. Despite the significant number of cases resulting in recovery, meningitis still causes deaths annually, especially bacterial etiology. Therefore, interventions such as training of professionals for case detection and reporting, improvement of vaccine coverage and overall health in the metropolitan region of Belém are necessary.